2011
DOI: 10.1186/1471-2458-11-114
|View full text |Cite
|
Sign up to set email alerts
|

Trends in self-reported prevalence and management of hypertension, hypercholesterolemia and diabetes in Swiss adults, 1997-2007

Abstract: BackgroundSwitzerland has a low mortality rate from cardiovascular diseases, but little is known regarding prevalence and management of cardiovascular risk factors (CV RFs: hypertension, hypercholesterolemia and diabetes) in the general population. In this study, we assessed 10-year trends in self-reported prevalence and management of cardiovascular risk factors in Switzerland.Methodsdata from three national health interview surveys conducted between 1997 and 2007 in representative samples of the Swiss adult p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
35
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 36 publications
7
35
2
2
Order By: Relevance
“…It should also be noted that the incidence of pre-existing hypertension was high (34%) in this population of 169 patients. In 2007, the prevalence of hypertension was 24.1% in Swiss adults [10]; however, in this study, the hypertension was self-reported and a predominantly healthy population was evaluated [11]. It is possibly that in a seriously ill patient population, such as those studied here, there might be ‘negative selection' of patients with a higher incidence of arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that the incidence of pre-existing hypertension was high (34%) in this population of 169 patients. In 2007, the prevalence of hypertension was 24.1% in Swiss adults [10]; however, in this study, the hypertension was self-reported and a predominantly healthy population was evaluated [11]. It is possibly that in a seriously ill patient population, such as those studied here, there might be ‘negative selection' of patients with a higher incidence of arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…However, the variation in definition of age brackets hinders any direct comparison between studies. In Switzerland, the prevalence of self-reported arterial hypertension in individuals 15 years or older increased from 22.1% to 24.2% in a 10-year period 12 . In the United States, self-reported arterial hypertension among individuals 18 years of age and older increased from 68.5% to 80.6% between 1988 and 2008 9,10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the Telephone Survey for Surveillance of Risk and Protective Factors for Chronic Non-Communicable Diseases (VIGITEL) showed that self-reported arterial hypertension increased evenly and significantly in the 27 State capitals included in the study, varying from 21.5% to 24.4% from 2006 to 2009 7 . Developed countries like Switzerland, Canada, and the United States have also shown increases in the prevalence of self-reported arterial hypertension 8,9,10,11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…In Switzerland, CVD mortality has dramatically decreased over the past three decades resulting in internationally very low rates (8). Counterintuitively, this apparently occurred without antecedent decrease in CVD-RF (10)(11)(12). We aimed at determining the impact of four traditional CVD-RF on CVD mortality in Switzerland and their population burden in terms of PAR and survival.…”
mentioning
confidence: 99%